Begonia naga (Begoniaceae, sect. Platycentrum), a new species from Nagaland, India - Krishna, Nikhil; Pradeep, Ayilliath Kuttiyeri; Jayakrishnan, Thachat (Phytotaxa, 2018)
A new species of Begonia, Begonia naga is described from Mokokchung, Nagaland, India. It belongs to the sect. Platycentrum. Detailed description, photographs, illustrations, distribution map and notes on habitat are provided.